A fast assessment method for thermal performance of naturally ventilated double-skin façades during cooling season. (April 2015) - Xue, Fei; Li, Xiaofeng
Highlights: We focus on the best thermal performance of DSF during the whole cooling season. Indoor heat gain through DSF is calculated separately and then summed up. The correlation between the heat gain and solar radiation intensity obeys power law. The coefficient of the power law ( RCI ) is determined by CFD method. The method was validated by two models with different openings. Abstract: Double-skin façades (DSFs) are promising and attractive building envelopes. DSFs can reduce the undesired heat gain during cooling season. However, due to complicated air flow and heat transfer in a DSF, economical and practical methods suitable for evaluating the thermal performance of a naturally ventilated DSF for the duration of a cooling season are still lacking. A large number of computational fluid dynamics (CFD) simulations are required to reach an assessment for a naturally ventilated DSF. This paper proposes a new fast calculation method. The proposed method significantly reduces the CFD simulation workload by establishing a correlation between indoor heat gain and solar radiation intensity. The novel calculation method demonstrated good computational accuracy. The results were verified by CFD models and were then applied to obtain the total indoor heat gain for a cooling season. This method could be used in optimization of DSFs.